SiMeti's Innovative Digital Media Strategy (Interactive Metamorphosis Simulation) to Improve Students' Engagement and Conceptual Understanding in Elementary Schools - Almaratus; Eges Triwahyuni; Hariyanto (Journal of Education Technology, 2025)
Low student engagement and conceptual understanding in Natural and Social Science (IPAS) learning, particularly on the topic of animal metamorphosis, remain a significant challenge. This condition is influenced by the use of conventional, teacher-centered learning methods that limit student participation and lead to suboptimal learning outcomes. This study aims to develop and evaluate interactive digital media called SiMeti (Interactive Simulation of Metamorphosis) to enhance elementary school students’ learning engagement and conceptual understanding. The research subjects consisted of 10 third-grade elementary school students as the trial group. The research method used was Research and Development (R&D) with the ADDIE model, including the stages of analysis, design, development, implementation, and evaluation. Data collection techniques included expert validation of content and media, student response questionnaires using a Likert scale, and cognitive tests in the form of pretests and posttests. Data were analyzed using descriptive statistics, N-Gain calculation, the Shapiro–Wilk normality test, the Wilcoxon Signed-Rank test, and Cohen’s d effect size analysis. The results showed that the media had a very high level of validity (content 91.1% and media 92%), student responses were in the high to very high category (85.27%), and there was a significant improvement in conceptual understanding (N-Gain = 0.76; p = 0.00195) with an effect size of 1.57, categorized as very large. Therefore, the SiMeti digital media is proven effective in improving elementary students’ engagement and conceptual understanding of the metamorphosis topic.